Non-convulsive status epilepticus in a patient with carbon-monoxide poisoning treated with hyperbaric oxygen therapy. Issue 6 (December 2016) - Marziali, Simone; Di Giuliano, Francesca; Picchi, Eliseo; Natoli, Silvia; Leonardis, Carlo; Leonardis, Francesca; Garaci, Francesco; Floris, Roberto
The presentation of carbon monoxide poisoning is non-specific and highly variable. Hyperbaric oxygen therapy is used for the treatment of this condition. Various reports show the occurrence of self-limiting seizures after carbon monoxide poisoning and as a consequence of hyperbaric oxygen therapy. Contrary to the seizures, status epilepticus has been rarely observed in these conditions. The exact pathophysiology underlying seizures and status epilepticus associated with carbon monoxide poisoning and hyperbaric oxygen therapy is not really clear, and some elements appear to be common to both conditions. We describe a case of non-convulsive status epilepticus in a patient with carbon monoxide poisoning treated with hyperbaric oxygen therapy. The mechanism, MRI findings and implications are discussed.